(untitled) (Acta Entomologica Serbica, 2022)
Perillus bioculatus (Fabricius, 1775) originates from North America, and was introduced to Europe at the beginning of the 20th century. The first findings of the species from nature in Serbia date back to 1996, after which the bug was not registered until 2018. After detecting one individual from 2018, we assumed that Perillus bioculatus would continue to spread throughout Serbia, and recent data have confirmed our suspicions. The paper presents literature and new findings from 2021 and 2022, as well as the conditioning of the spread of the species by the expansion of the range of new prey Ophraella communa LeSage, 1986 - also a non-native insect species in Europe, which was recorded in Serbia for the first time in 2020. In almost all localities from 2022, P. bioculatus was recorded on ragweed together with O. communa.